Efforts To Increase Interest In Learning Table Tennis Through Games Method In Pjok Learning In Class Viii A Smpn 21 Kota Bengkulu - Dendi Sapril; Utama, Eko Putra; Dewi, Citra (Journal of Physical Education and Sports, 2025)
This study aims to determine the Efforts to Increase Interest in Learning Table Tennis Through the Games Method in Pjok Learning in Class Viii A SMPN 21 Bengkulu City. This type of research is classroom action research, the research conducted intends to find information about the implementation of the learning model delivered by classroom action treatment, namely the stages of the cycle in learning. The results of the research that has been done, it can be concluded that the action with the games method in learning PJOK can increase interest in learning. It is proven that it can increase with the data obtained in each cycle, namely in cycle 1 the first meeting was 62%, cycle 1 the second meeting was 69%, cycle 2 the first meeting was 72%, cycle 2 the second meeting was 93%. This action process is part of the class action process in the form of table tennis learning activities through the games method. This research proves that the games method can increase students' interest in learning table tennis in class VIII A SMPN 21 Bengkulu City.